An inverted CAV1 (caveolin 1) topology defines novel autophagy-dependent exosome secretion from prostate cancer cells. Issue 9 (2nd September 2021) - Ariotti, Nicholas; Wu, Yeping; Okano, Satomi; Gambin, Yann; Follett, Jordan; Rae, James; Ferguson, Charles; Teasdale, Rohan D.; Alexandrov, Kirill; Meunier, Frederic A.; Hill, Michelle M.; Parton, Robert G.
ABSTRACT: CAV1 (caveolin 1) expression and secretion is associated with prostate cancer (PCa) disease progression, but the mechanisms underpinning CAV1 release remain poorly understood. Numerous studies have shown CAV1 can be secreted within exosome-like vesicles, but antibody-mediated neutralization can mitigate PCa progression; this is suggestive of an inverted (non-exosomal) CAV1 topology. Here we show that CAV1 can be secreted from specific PCa types in an inverted vesicle-associated form consistent with the features of bioactive CAV1 secretion. Characterization of the isolated vesicles by electron microscopy, single-molecule fluorescence microscopy and proteomics reveals they represent a novel class of exosomes ~40 nm in diameter containing ~50-60 copies of CAV1 and, strikingly, are released via a non-canonical secretory macroautophagy/autophagy pathway. This study provides novel insights into a mechanism whereby CAV1 translocates from a normal plasma membrane distribution to an inverted secreted form implicated in PCa disease progression. Abbreviations: 3-MA: 3-methyladenine; APEX: a modified soybean ascorbate peroxidase; ATG5: autophagy related 5; ATG9A: autophagy related 9A; ATG12: autophagy related 12; BHK: baby hamster kidney; C-exosomes: caveolin-exosomes; CAMKK2/CAMKKβ: calckum/calmodulin dependent protein kinase kinase 2; CAV1: caveolin 1; DAB: 3, 3′-diaminobenzidine; DAPK: death associated protein kinase; EEA1: early endosome antigen 1; EM: electron microscopy; FCS: fluorescence correlation spectroscopy; GBP: GFP/YFP-binding peptide; GFP: green fluorescent protein; GOLGA2: golgin A2; ILVs: intralumenal vesicles; LC3: microtubule-associated protein 1 light chain 3; MBP: maltose binding protein; MTORC1: mechanistic target of rapamycin kinase complex 1; MVBs: multivesicular bodies; PBS: phosphate-buffered saline; PCa: prostate cancer; PI3K: phosphoinositide 3-kinase; PM: plasma membrane; SFM: serum-free medium; TSG101: tumor susceptibility 101; WCL: whole cell lysates; WT: wild type; YFP: yellow fluorescent protein; βoG: β-octylglucoside